Vibrational spectroscopic behavior of K7[Ti2W10PO40]⋅6H2O: an interesting and potent antiviral polyoxometalate - Baran, Enrique José (2021)
We prepared K7[Ti2W10PO40]⋅6H2O, containing a hetero-polyoxoanion with Keggin-type structure, which shows interesting pharmacological properties. The infrared and Raman spectra of the compound in the solid state were recorded and briefly analyzed in comparison with those of other polyoxoanions with related structures.